Oxidative Stress Biomarkers and Antioxidant Protocols - Armstrong, Donald; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2002)
Oxidative stress has been linked to a variety of medical problems, including cardiovascular disease, cancer, arthritis, diabetes, and aging. Drawing on the growing volume of research into the impact of oxidative stress on pathophysiological mechanisms, Donald Armstrong updates and expands his highly praised Free Radical and Antioxidant Protocols (Humana, 1998) with a collection of new and valuable methods for evaluating the perturbations in cell function resulting from increased oxidative stress. Presented in a user-friendly, step-by-step format by accomplished investigators from prestigious universities, institutes, and laboratories around the world, these readily reproducible techniques cover both free radical-derived and antioxidant biomarkers. The methodologies demonstrated include ELISA, HPLC, infrared spectroscopy, gas chromatography-mass spectroscopy, immunoblotting, electroelution fractionation, isoelectric focusing, voltammetry, and electron paramagnetic resonance imaging. Special emphasis is given to the separation of complex mixtures of plant antioxidants, soft drug design to protect from toxic oxidative metabolites, in vitro oxidation conditions, and correcting for random measurement error to improve statistical interpretation. A soon-to-be-published companion volume, Oxidants and Antioxidants: Ultrastructure and Molecular Biology Protocols (Humana, 2002), contains state-of-the-art molecular and ultrastructural methods that expand the total number of protocols to 109 assays. Cutting-edge and highly practical, Oxidative Stress Biomarkers and Antioxidant Protocols provides many powerful new tools for detecting oxidative stress and for investigating the possibilities for therapeutic intervention monitoring in a variety of serious diseases.
Techniques for Free Radical Derived Biomarkers -- Human Xanthine Oxidoreductase Determination by a Competitive ELISA -- Simultaneous Determination of Polyunsaturated Fatty Acids and Corresponding Monohydroperoxy and Monohydroxy Peroxidation Products by HPLC -- Determination of Products of Lipid Oxidation by Infrared Spectroscopy -- Detection of Docosahexaenoic Acid Hydroperoxides in Retina by Gas Chromatography/Mass Spectrometry -- Detection of Lipid Hydroperoxide-Derived Protein Modification with Polyclonal Antibodies -- Techniques for Determining the Metabolic Pathways of Eicosanoids and for Evaluating the Rate-Controlling Enzymes -- Mass Spectrometric Quantification of F2-Isoprostanes as Indicators of Oxidant Stress -- Formation of Apolipoprotein AI-AII Heterodimers by Oxidation of High-Density Lipoprotein -- Detection of Certain Peroxynitrite-Induced DNA Modifications -- Hydroxyl and 1-Hydroxyethyl Radical Detection by Spin Trapping and GC-MS -- Analysis of Aliphatic Amino Acid Alcohols in Oxidized Proteins -- Rapid Determination of Glutamate Using HPLC Technology -- A Rapid Method for the Quantification of GSH and GSSG in Biological Samples -- Protein Carbonyl Measurement by ELISA -- N ?-(carboxymethyl)lysine (CML) as a Biomarker of Oxidative Stress in Long-Lived Tissue Proteins -- Measurement of S-Glutathionated Hemoglobin in Human Erythrocytes by Isoelectric Focusing Electrophoresis -- Oxidation of Cellular DNA Measured with the Comet Assay -- Measurement of DNA Double-Strand Breaks with Giant DNA and High Molecular-Weight DNA Fragments by Pulsed-Field Gel Electrophoresis -- Evaluation of Antibodies Against Oxygen Free Radical-Modified DNA by ELISA -- Techniques for Antioxidant Biomarkers -- Simultaneous Analysis of Multiple Redox-Active Metabolites from Biological Matrices -- Determination of Uric Acid in Urine by Fast-Scan Voltammetry (FSV) Using a Highly Activated Carbon Fiber Electrode -- Measurement of ?-Tocopherol Turnover in Plasma and in Lipoproteins Using Stable Isotopes and Gas Chromatography/Mass Spectrometry -- Analysis of Tocotrienols in Different Sample Matrixes by HPLC -- Measurement of ?-Carotene15,15?-Dioxygenase Activity by Reverse-Phase HPLC -- Ubiquinol/Ubiquinone Ratio as a Marker of Oxidative Stress -- Catechol- and Pyrogallol-Type Flavonoids -- Pyruvate Dehydrogenase Complex as a Marker of Mitochondrial Metabolism -- Ceruloplasmin Detection by SDS-PAGE, Immunoblotting, and In Situ Oxidase Activity -- Metallothionein Determination by Isocratic HPLC with Fluorescence Derivatization -- Quantification of Oxidized Metallothionein by a Cd-Saturation Method -- Fractionation of Herbal Medicine for Identifying Antioxidant Activity -- Designing Safer (Soft) Drugs by Avoiding the Formation of Toxic and Oxidative Metabolites -- Statistical Correction of the Area Under the ROC Curve in the Presence of Random Measurement Error and Applications to Biomarkers of Oxidative Stress.
Keywords: Biochemistry; Biochemistry, general